The Effect Of Communication And Work Discipline On The Work Productivity Of Employees In Production At PDAM Tirta Galuh, Ciamis District - Renaldy Anamal Nugraha; Barin Barlian; Nita Fauziah Oktaviani (Journal of Indonesian Management, 2023)
The purpose of this study was to find out and analyze the description of communication, work discipline and work productivity of production employees at PDAM Tirta Galuh, Ciamis Regency. The effect of communication and work discipline simultaneously on the work productivity of production employees at PDAM Tirta Galuh, Ciamis Regency. The effect of partial communication on the work productivity of production employees at PDAM Tirta Galuh, Ciamis Regency. The effect of work discipline partially on the work productivity of production employees at PDAM Tirta Galuh, Ciamis Regency. This research includes quantitative research in the sense that in this study it uses numbers, starting from data collection to interpreting data with statistical tests. The data collection technique used was a survey method. The data analysis technique used was descriptive statistical analysis and multiple linear regression tests. The results showed that communication was included in the very good category, Work Discipline was included in the good category, and Work Productivity for PDAM Tirta Galuh Ciamis employees was included in the good category. There was a significant effect simultaneously of Communication and Work Discipline on Work Productivity for PDAM Tirta Galuh Ciamis employees. There was a significant influence partially Communication on Work Productivity to employees of PDAM Tirta Galuh Ciamis. There is a partial significant effect of Work Discipline on Work Productivity for PDAM Tirta Galuh Ciamis employees.